Live cinema: narrativas de autoria coletiva em tempo real: da fase poética subjetiva a produção de narrativas objetivas - Rodrigues, Alexandre Coronato (2015)
This study aims to understand the current state of the production processes of collective narratives in real-time and identify a different way, not yet experienced, to create Live Cinema pieces. Therefore, it starts from the narrative concept definition supported by the philosophical theories of Rolland Barthes and Walter Benjamin added to the aesthetic theories of digital media of Lev Manovich, the analysis of the types of cinematographic narratives of André Parente and authorship concept discussion according to researchers Lucia Santaella, Arlindo Machado and Antonio Miranda. From these definitions we identified the structural parameters of contemporary digital storytelling, which allowed the analysis of four current examples of collective production of stories in real time, distinguishing them as the kind of narrative created and the depth of the collective participation in its creation. As a result, this paper presents the specification of production real-time collective narratives system, which proves the discovery revealed by analysis and points the universe of possibilities that arise with the advent of digital technologies of information processing